Randomized Phase I Healthy Volunteer Study of UTTR1147A (IL‐22Fc): A Potential Therapy for Epithelial Injury. Issue 1 (12th August 2018) - Rothenberg, Michael E.; Wang, Yehong; Lekkerkerker, Annemarie; Danilenko, Dimitry M.; Maciuca, Romeo; Erickson, Rich; Herman, Ann; Stefanich, Eric; Lu, Timothy T.
Abstract : Most treatments for epithelial injury target hematopoietic mechanisms, possibly causing immunosuppression. Interleukin (IL)‐22 promotes tissue regeneration, acting directly on epithelial cells. UTTR1147A, a human IL‐22Fc (immunoglobulin G (IgG)4) fusion protein, activates IL‐22 signaling. This phase I placebo‐controlled trial of single, ascending, i.v. (1–120 μg/kg) and s.c (3–120 μg/kg) doses of UTTR1147A analyzed its effects on safety, tolerability, pharmacokinetics, and pharmacodynamic biomarkers in healthy volunteers. Most adverse events (AEs) were mild or moderate. The maximum tolerated i.v. dose in healthy volunteers was 90 μg/kg. Predominant AEs were dose‐dependent reversible skin effects consistent with IL‐22 pharmacology. UTTR1147A exposure increased approximately dose‐proportionally, with a half‐life of 1 week. IL‐22 biomarkers (regenerating islet protein 3A (REG3A), serum amyloid A (SAA), and C‐reactive protein (CRP)) increased dose‐dependently. Neither inflammatory symptoms and signs nor cytokines increased with CRP elevations. UTTR1147A demonstrated acceptable safety, pharmacokinetics, and IL‐22R engagement, supporting further clinical development.